Meningkatkan Hasil Belajar Peserta Didik Pembelajaran Agama Islam Menggunakan Metode Diferensiasi di Kelas X TKJ SMK Rosma Karawang - Vani, Vani novariyanti; Sinta Rakasiwi; Rasyid Mulqisani; Nur Aini Farida; M. Makbul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to improve student learning outcomes in Islamic religious learning using the differentiation method in Class X TKJ SMK Rosma Karawang. The method used in this research is a qualitative descriptive research approach using the differentiation method. The results of this research show that the application of the differentiation method in learning Islam in class 10 TKJ Rosma Vocational School Karawang has a positive impact on student learning outcomes. The experimental group that received differentiation method treatment showed a significant increase in learning outcomes compared to the control group that received conventional learning.